Bacterial periplasmic nitrate and trimethylamine-N-oxide respiration coupled to menaquinol-cytochrome c reductase (Qcr): Implications for electrogenic reduction of alternative electron acceptors. Issue 1 (December 2018) - Garg, Nitanshu; Taylor, Aidan; Kelly, David
Abstract The periplasmic reduction of the electron acceptors nitrate (E m +420 mV) and trimethylamine-N-oxide (TMAO;E m +130 mV) by Nap and Tor reductases is widespread in Gram-negative bacteria and is usually considered to be driven by non-energy conserving quinol dehydrogenases. TheEpsilonproteobacterium Campylobacter jejuni can grow by nitrate and TMAO respiration and it has previously been assumed that these alternative pathways of electron transport are independent of the proton-motive menaquinol-cytochromec reductase complex (QcrABC) that functions in oxygen-linked respiration. Here, we show that aqcrABC deletion mutant is completely deficient in oxygen-limited growth on both nitrate and TMAO and is unable to reduce these oxidants with physiological electron donors. As expected, the mutant grows normally on fumarate under oxygen-limited conditions. Thus, the periplasmic Nap and Tor reductases receive their electrons via QcrABC inC .jejuni, explaining the general absence of NapC and TorC quinol dehydrogenases inEpsilonproteobacteria . Moreover, the specific use of menaquinol (E m −75 mV) coupled with a Qcr complex to drive reduction of nitrate or TMAO against the proton-motive force allows the process to be electrogenic with a H+ /2e− ratio of 2. The results have general implications for the role of Qcr complexes in bacterial oxygen-independent respiration and growth.